The Role of Work Satisfaction and Motivation for Improving Work Enthusiasm of Civiil Servants in the Sorkam District Government Environment - Kaharuddin; Simamora, Fauziah Nur (Jurnal Ilmiah Sumber Daya Manusia, 2026)
The resent study aims to analyze the role of satisfaction and motivation  for improving the work enthusiasm of civil servants  in the Sorkam Subdistrict Government Office. This study uses a quantitative approach with a descriptive-correlational research design, with a sample size of 32 people. Data collection techniques were conducted through closed questionnaires, and data analysis, namely normality tests, multicollinearity tests, multiple regression analysis, determination coefficients, F and t tests using SPSS version 26 software. The results showed that job satisfaction and motivation had a positive and significant effect on the work motivation of civil servants.Some factors such as clarity of tasks, support from superiors, rewards for performance, and opportunities for self-actualization were proven to be able to substantially increase work enthusiasm. The findings indicate that strategies to increase work enthusiasm need to integrate psychological and managerial approaches in building work enthusiasm, but with a more humane managerial approach that pays attention to the emotional satisfaction and psychological motivation of employees.